MEMPOSISIKAN ANAK YANG LAHIR DILUAR NIKAH SECARA HUKUM ISLAM - Henderi Kusmidi (Universitas Islam Negeri Fatmawati Sukarno, 2016)
Humans are the only creatures who are entrusted with managing this earth as His caliph. Therefore the existence of human beings should be sustained. In this regard humans are given the ability to have sexual intercourse for the sake of the process of regeneration of the human species in a sustainable manner. Or with other terms of sexuality is a universal process media in the context of the preservation of creation. Not only that, sexual pleasure in Islam is considered as being privileged. So life with legitimate partner (married) are more honored than the single life. Thus aqad marriage essentially as a means true, dignity and respect for every human being in order to channel their biological desires. This is where Islam prohibits any form of sexual relations that are not done correctly and with dignity as adultery, sodomy, and so on. Because in addition to violating the rules of religion, is also incompatible with the position of the human beings with dignity and respect. Even adultery by Divine religions is considered as one of the biggest and dirtiest forms of crimes against humanity, while the base of the onset of the destruction of the joints civic and adultery are also categorized as one of the major sins